Pajak Daerah dan Restribusi Daerah (PDRD) Dikaitkan dengan Pertumbuhan Investasi - Fernando Hariandja (Universitas Negeri Surabaya, 2020)
Tax has a very important role in the life of the country, especially in the implementation of development. Tax revenue is the payment of contributions by the people to the government that are regulated in the law without direct compensation. As is the case with central government taxes, Regional Taxes have an important role in implementing state/government functions, both in the functions of regulation, budgeting, redistributive, and allocation of resources and a combination of the four. A good local tax in principle must provide adequate income for regions with the level of fiscal autonomy they have. Some regions do accommodate the function of revenue and regulation in the formulation of Regional Tax policies. The step that has not been widely considered by the regions is the provision of Regional Tax incentives to attract investment in the regions. In the current era of regional autonomy, regions are given greater authority to regulate and manage their own households. The aim is to bring government services closer to the community. Anyway, President Joko Widodo often complained about the small value of investment coming into Indonesia, one of which is caused by the irrationality of the Regional Tax rates in the eyes of investors. This paper analyzes what policies the government has taken towards PDRD, which are considered to have many of these problems to increase investment growth in Indonesia. To overcome this, the government has made several efforts, one of which is to establish the Omnibus Law. However, the formation of the Omnibus Law itself actually unwittingly has the potential to erode the regional authority to look for sources of locally-generated revenue (PAD). If PAD is reduced, automatically the level of regional dependence on funds from the central government will be even greater, and if PAD is low, then the level of local government public service to the community is also feared to be reduced.